Effectiveness of technology in midwifery education for enhancing knowledge and clinical skills - Yohana Filiberta Lumu Ladjar; Ari Indra Susanti (Inovasi Kurikulum)
Multimedia has positively impacted knowledge transfer, emphasizing the importance of collaborative learning and interactive tools in improving educational outcomes. E-learning contributes significantly to knowledge transfer and skill enhancement among nurses and midwives. This study aims to determine the effectiveness of technology in midwifery education. This literature review uses a descriptive analysis approach. Article searches used keywords across three databases that met the inclusion criteria. As a result, 17 articles were selected as references for this study. The article specifically discusses the use of technology in education from three themes: knowledge enhancement, skill improvement, and clinical readiness of midwifery students. From the collected articles, six concluded that technology influences knowledge enhancement, ten agreed that technology can improve students' skills, and four believed that technology can increase students' clinical readiness. The study concludes that technology plays a vital role in equipping midwifery students with enhanced knowledge and skills and fostering their clinical practice readiness in maternal and child health care.